2011
DOI: 10.1093/mp/ssq078
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Reveals Post-Translational Mechanisms for Cold-Induced Metabolic Changes in Arabidopsis

Abstract: Cold-induced changes of gene expression and metabolism are critical for plants to survive freezing. Largely by changing gene expression, exposure to a period of non-freezing low temperatures increases plant tolerance to freezing-a phenomenon known as cold acclimation. Cold also induces rapid metabolic changes, which provide instant protection before temperature drops below freezing point. The molecular mechanisms for such rapid metabolic responses to cold remain largely unknown. Here, we use two-dimensional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 73 publications
(131 reference statements)
1
29
0
Order By: Relevance
“…Maltose is hydrolyzed from starch in the chloroplast and could be exported into the cytosol by its specific transporter MEX1 and catabolized by DPE2. Interestingly, recent studies suggested that both MEX1 and DPE2 influence plant cold tolerance by modulating the allocation of maltose (Li et al 2011;Lloyd et al 2004;Purdy et al 2013). Our results revealed that starch degradation is important for LT stimulation during CA period in tea plant.…”
Section: Ca Activates Starch Degradation In Response To Coldsupporting
confidence: 47%
See 1 more Smart Citation
“…Maltose is hydrolyzed from starch in the chloroplast and could be exported into the cytosol by its specific transporter MEX1 and catabolized by DPE2. Interestingly, recent studies suggested that both MEX1 and DPE2 influence plant cold tolerance by modulating the allocation of maltose (Li et al 2011;Lloyd et al 2004;Purdy et al 2013). Our results revealed that starch degradation is important for LT stimulation during CA period in tea plant.…”
Section: Ca Activates Starch Degradation In Response To Coldsupporting
confidence: 47%
“…The contributions of these genes to cold tolerance have been verified in different species. Several reports show that LT induces starch degradation, and the involved main enzymes coding genes in this pathway including glucan water dikinase (GWD), beta-amylase (BAM) as well as its downstream genes, such as maltose transporter (maltose excess1, MEX1) and disproportionating enzyme 2 (DPE2), are differentially regulated and facilitate plant cold responses Guy 2004, 2005;Li et al 2011;Purdy et al 2013;Yano et al 2005). For instance, PtrBAM1 has been identified as a CBF regulon, which functions under cold conditions (Peng et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2D-DIGE has been successfully applied to investigate symbiosis- and pathogenesis-related protein in Medicago truncatula [16, 17] and to study the impact of abiotic stresses such as drought in oak [18], frost in Arabidopsis [19], ozone, and heavy metals in poplar [2022]. …”
Section: Gel-based Proteomicsmentioning
confidence: 99%
“…Alteration of energy metabolism under cold stress conditions can be affected by enzymes involved in glycolysis (Yan et al, 2006) and the tricarboxylic acid (TCA) cycle (Li et al, 2011). SCaMC mediates ATP-Mg/Pi exchange and plays important roles in energy metabolism (Yang et al, 2014).…”
Section: Involvement In Energy Metabolismmentioning
confidence: 99%